Brain Anatomy of Asperger's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Brain anatomy and sensorimotor gating were compared in 21 adults with Asperger's syndrome and 24 controls, all of normal IQ, aged 18-49 years.